An Analysis of Translation Shift of Adjective Phrases in the Subtitle of 2019 Movie “Jumanji: The Next Level” - Mutia Aryanti; Dyah Raina Purwaningsih; Raden Pujo Handoyo (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2021)
The research aims to identify the translation shift and describe the equivalence of adjective phrases found in the Jumanji: The Next Level movie and its subtitling. To get the analysis result, translation shift proposed by Catford (1965) and degree of equivalence proposed by Bell (1991) are used in this research. The research is conducted by using descriptive qualitative method in analyzing the data and total sampling technique. The data of this research are 104 English adjective phrases taken from Jumanji: The Next Level movie and their subtitles in Indonesia that is translated by Pein Akatsuki. The results of this research for the types of translation shift are 2 level shift, 59 structure shift, 19 class shift, 22 unit shift, and 2 intra system shift. Meanwhile, the result for the equivalence are 64 complete meaning, 3 increased meaning, 26 decreased meaning, and 11 non equivalent meaning in the category of different meaning. This current research explores adjective phrase that has not been much discussed by other scholars.